1998
DOI: 10.1074/jbc.273.43.27879
|View full text |Cite
|
Sign up to set email alerts
|

Mutation at Histidine 338 of gp91 Depletes FAD and Affects Expression of Cytochrome b 558 of the Human NADPH Oxidase

Abstract: phox . This was in agreement with the finding that a single base substitution (C1024 to T) changed His-338 to Tyr in gp91 phox in a predicted FAD-binding domain of the flavocytochrome model. The loss of FAD could not be corrected even after addition of reagent FAD or a FADrich dehydrogenase fraction isolated from normal neutrophils to the patient's membranes, in a reconstitution in vitro with normal cytosol. These results indicate that His-338 is a very critical residue for FAD incorporation into the NADPH oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 53 publications
2
33
0
Order By: Relevance
“…We have shown that an antibody against human gp91 phox C-terminus 28) seemed able to recognize guinea pig Nox1. 20) The same antibody, however, did not cross-react with human Nox1 protein, which required the raising of another antibody for detecting Nox1 in Caco-2 cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have shown that an antibody against human gp91 phox C-terminus 28) seemed able to recognize guinea pig Nox1. 20) The same antibody, however, did not cross-react with human Nox1 protein, which required the raising of another antibody for detecting Nox1 in Caco-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…17) The antibodies against C-terminal peptides of human gp91 phox and p22 phox were the same as in. 28) Deglycosylation of N-linked carbohydrates of the large subunits of cytochrome b 558 from human (gp91 phox ) and guinea pig (ca. 62 kDa) neutrophils was performed with peptide: N-glycosidase F (PNGase F, New England Biolabs), as described.…”
Section: Expression and Purification Of Recombinant P67mentioning
confidence: 99%
See 3 more Smart Citations